The Potential of Multifrequency Spaceborne DInSAR Measurements for the Retrieval of Snow Water Equivalent - Kristina Belinska; Georg Fischer; Giuseppe Parrella; Irena Hajnsek (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2024)
The snow water equivalent (SWE) is the amount of water contained in a snow pack and is, therefore, an important variable for hydrological and climate models. Differential interferometric synthetic aperture radar (DInSAR) techniques can relate the interferometric phase of two repeat-pass SAR acquisitions to the SWE change between them. However, only a limited interval of SWE change can be retrieved unambiguously due to phase wraps of the interferometric phase. This interval strongly depends on the wavelength of the radar wave. Additional information, for instance ground measurements of SWE, is required to identify whether the SWE change exceeded that interval and to correct the phase wraps. In the study, the performance of X-, C-, and L-bands spaceborne SAR acquisitions for SWE estimation is analyzed, demonstrating the advantages and limitations of different frequencies. Shorter wavelengths show a higher accuracy for SWE estimations, while longer wavelengths are less affected by phase wraps. A multifrequency approach is proposed where L-band acquisitions are used to correct the phase wraps in the C-band SWE retrieval. The accuracy decreases slightly, but this approach allows a more robust SWE retrieval without the need of additional ground measurements. For current spaceborne SAR missions, temporal decorrelation and phase calibration are limiting factors.